Effect of exogenous proline on the production and partitioning of dry matter and on the organic carbon content at different stages of the tomato plant - de Oliveira, Jailson (2025)
Water limitation is one of the most serious problems in tomato production, responsible for a significant reduction in productivity and fruit quality. In this context, the application of exogenous proline may be an alternative for plants to deal with possible water stress. The objective of this work was to evaluate the production, dry matter mass partition and organic carbon content of the tomato cultivar “Vivacy”, cultivated with doses of proline and irrigated every seven days. A randomized block design was used, with four replications and a 2 x 3 + 1 factorial arrangement. The factors consisted of 2 doses of proline (100 and 150 mg L-1), 3 application times (1, 3 and 6 days after irrigation) and a control without proline application. Data analysis showed a significant difference in the variables analyzed, revealing that the application of proline influenced the production and partition of dry matter mass of tomato plants. However, no significant difference was found in some variables, although the application of treatments showed superior results compared to the control. Proline sprayed at a dose of 100 mg L-1 increases the dry matter mass and organic carbon content in tomato plants during the fruiting and end-of-cycle phases, in addition to contributing to greater dry matter partitioning for the fruits.